EL RETABLO EN MURCIA DURANTE EL SIGLO XVII: ALGUNOS EJEMPLOS REPRESENTATIVOS DE LORCA - Segado Bravo, Pedro (Imafronte, 1994)
The beginning of the 17th century witnessed the predominance in the Baroque of Lorca, particularly with regard to altarpieces, of the influence of late Renaissance enriched by two other characteristic trends: the Herrerian, originating through the Court, and the Granadine, directly from the city of Granada, which is of unquestionable importance in Spanish Renaissance. It was not until the second half of the 17th century that a Levantine influence, introduced by Orihuela artists familiar with Italian Baroque, was incorporated into the Baroque of Lorca. During the 17th century, Lorca’s altarpieces were influenced by all three stylistic trends, the variations of which with time were to shape the definitive style. But this definitive style, which is and can be called true Baroque, did not really appear in my opinion until the end of the 17th century.